Konflik Peran Ganda dengan Prokrastinasi Akademik Pada Mahasiswa Polri - Kurniawan, Kurniawan; Rahayu, Diah (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
Academic procrastination is a phenomenon that often occurs, especially in students who have multiple roles as well as students in the National Police. This study aims to empirically examine whether or not there is a relationship between work family conflict and academic procrastination of Polri students at Mulawarman University. The method used is correlational quantitative, the number of subjects is 96 Police students who were selected by total sampling technique. Data were collected using the academic procrastination and work family conflict scale adopted from previous studies with the reliability level of the academic procrastination scale = 0.852 and the work family conflict scale = 0.900. The data analysis technique using the Pearson Product Moment correlation test resulted in a calculated r value = 0.584 and p = 0.000 <0.05. These results show a fairly strong relationship between work family conflict and academic procrastination, meaning that the higher the perceived work family conflict, the higher the academic procrastination carried out by Polri students at Mulawarman University.Prokrastinasi akademik merupakan fenomena yang sering terjadi terutama pada mahasiswa yang memiliki peran ganda seperti halnya pada mahasiswa yang juga berstatus sebagai anggota Polri. Penelitian ini bertujuan untuk menguji secara empirik ada atau tidaknya hubungan antara konflik peran ganda terhadap prokrastinasi akademik pada mahasiswa Polri di Universitas Mulawarman. Metode yang digunakan kuantitatif korelasional, jumlah subjek 96 orang mahasiswa Polri yang dipilih dengan teknik total sampling. Data dikumpulkan menggunakan skala prokrastinasi akademik dan konflik peran ganda yang diadopsi dari penelitian sebelumnya dengan tingkat reliabilitas skala prokrastinasi akademik = 0.852 dan skala konflik peran ganda = 0.900. Teknik analisa data menggunakan uji korelasi Pearson Product Moment menghasilkan nilai r hitung = 0.584 dan p = 0.000 < 0.05. Hasil ini menunjukkan hubungan yang cukup kuat antara konflik peran ganda dengan prokrastinasi akademik, artinya semakin tinggi konflik peran ganda yang dirasakan maka semakin tinggi pula prokrastinasi akademik yang dilakukan oleh mahasiswa Polri di Universitas Mulawarman.